2-D Physical Modeling to Measure the Effectiveness of Perforated Skirt Breakwater for Short-Period Waves - Harman Ajiwibowo (Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
The effectiveness of a breakwater can be measured by quantifying the transmission coefficient (KT). The smaller the coefficient, the better the performance of the breakwater. A physical modeling on the proposed breakwater was conducted to identify the coefficient of Perforated Skirt Breakwater (PSB). The PSB model was tested in 2-D wave flume at Ocean Wave Research Laboratory FTSL ITB, to obtain the effectiveness of PSB for short-period waves (prototype periods, Tp= 4 second and smaller). The scaling of PSB models applies the principle of Froude Similarity, where the Froude number in model equals to the Froude number in prototype (Frm=Frp). The flume is equipped with 5 resistance-type wave probes and 8-channel DAS (Data Acquisition System). Wave heights (H) and wave periods (T) data were observed both manually by visual observation and wave probes readings (processed later with method of